From formalin to thiel embalming: What changes? One anatomy department's experiences. Issue 5 (13th February 2013) - Eisma, R.; Lamb, C.; Soames, R.W.
<x xml:space="preserve">Abstract</x> In 2009, the Centre for Anatomy and Human Identification started Thiel embalming on a small scale to assess (i) the suitability for our current teaching in which long‐lasting dissection courses are key, (ii) the potential for new collaborations and activities, and (iii) the practical implications of changing our embalming method from formalin to Thiel. Twenty six Thiel‐embalmed cadavers have been used for dissection by staff and students on a taught MSc course, as a model for clinical and surgical training, and increasingly as a model for evaluation of new medical devices and procedures. Our experiences with dissection were mostly positive especially for teaching the musculoskeletal system. Internal organs handle differently from formalin‐fixed organs and dissection manuals need to be adjusted to reflect this. Durability of the cadavers was not an issue, though changes are seen over time due to gradual fluid loss. We have started new collaborations related to postgraduate anatomy teaching and advanced training in surgical and clinical skills. In general, feedback is very positive and demand for cadavers outstrips our current limited supply. Thiel‐embalmed cadavers were found to provide a unique opportunity for evaluation of medical products especially in areas where no suitable alternative model is available, and without the complications associated with clinical testing. This has resulted in new collaborations and research projects. As a result Thiel‐embalmed cadavers are used for longer and for more activities than formalin cadavers: this requires changes in our procedures and staff roles. Clin. Anat. 26:564–571, 2013. © 2013 Wiley Periodicals, Inc.